Adverse drug events associated with sodium zirconium cyclosilicate: A real-world pharmacovigilance study based on the FAERS database - Yinrui Fang; Zilun Wu; Qian Wu; Gangyi Chen (PLoS ONE, 2025)
Background Sodium zirconium cyclosilicate (SZC, Lokelma) is a novel hyperkalemia therapy, but comprehensive real-world safety data are lacking. This study aimed to characterize SZC-associated adverse events (AEs) using post-marketing surveillance. Research Design and Methods AE reports for SZC/Lokelma were extracted from the FDA Adverse Event Reporting System (FAERS) (2004–2023). Four disproportionality algorithms (ROR, PRR, BCPNN, MGPS) identified safety signals. Significant system organ class (SOC) signals required ROR ≥ 2; preferred term (PT) signals met all algorithm thresholds, with false discovery rate adjustment. Results Among 1,564 AE reports (49% males, 29.5% females), four SOCs showed significant signals: metabolism/nutrition, renal/urinary, cardiac, and general disorders. Eighteen PT signals included hypokalemia, cardiac failure, and hypertension. Previously unreported AEs (e.g., ileus, ventricular fibrillation) emerged. AEs peaked early (41.87% within 30 days). Subgroup analyses confirmed robustness. Conclusions This study highlights both previously recognized and potentially novel adverse event signals associated with SZC, particularly during the early phase of treatment. While limited by the inherent constraints of spontaneous reporting systems—such as underreporting and missing data—our findings suggest that clinicians may consider closer monitoring of metabolic, renal, and cardiac adverse events during initial therapy. Observed early signals merit further validation in prospective studies, while long-term risks remain to be clarified.